The regulation of the financial sector in China: a tale of two governments*. Issue 2 (3rd July 2018) - He, Weiping
ABSTRACT: This article discusses an important regulatory phenomenon in China's securities markets: regulation by local governments. Multi-level financial market regulation is an intrinsic part of the Chinese financial regulatory system, and the article looks at the nature and dynamics of the role played by local governments, and interactions between the central government and local governments. The article commences with a review of the degrees of economic decentralisation and political centralisation evident in China. The article then discusses the struggle between local governments and the central government that arise from competing objectives. After reviewing regulatory powers of local governments in general, and their powers to regulate credit companies, financing guarantor companies, private capital management companies, and regional markets, the article examines the competition between local governments for financial resources and its implications.